PENGEMBANGAN PENILAIAN AUTENTIK BERBASIS KURIKULUM 2013 DI KELAS IV SEKOLAH DASAR NEGERI KOTA PEKANBARU - Zaka Hadikusuma (JURNAL TEMATIK, 2015)
This study aimed to 1) determine whether there was an authentic assessment in teacher and student grade book IV, 2) develop an authentic assessment tool that does not exist in the book of teachers and students based on curriculum assessment in 2013 to the theme of hero in the fourth grade elementary school Pekanbaru , 3) determine how the accuracy of authentic assessment tool developed in accordance with the hero theme based Jugdment experts, and 4) determine how the validity and reliability of authentic assessment tool developed. This study was conducted from December to February 2015, this type of research is the development of research that uses the type of formative research. The subjects in this study consists of five subject matter experts, one expert Thematic, and one expert evaluation in order to assess the accuracy of the assessment instruments developed. Data on quality of product development were collected by observation sheet and questionnaire validation. The data collected was analyzed by qualitative descriptive analysis techniques. assessment instrument that does not exist in the book of teachers and students on the theme of "hero" is the attitude assessment instruments. The results of the expert validation overall scoring average was 95.63 very good category. The results of the validation of five components 1) objectivity, 2) systematic, 3) construction, 4) language, 5) Practicality. This suggests that authentic assessment instrument based curriculum developed in 2013 based on the results of the validation performed by experts can be expressed Excellent and are appropriate to be used or worn for menilaian student attitudes during the learning process in the classroom. The test is a test of the validity and reliability of assessment instruments developed. The validity test with 2 way teachers are given instruments and assigned to assess students simultaneously. On the validity of the test is performed 2 trials, namely small-scale trials 2 and 6 teachers of students and large-scale trials 2 teachers and 20 students. Assessment instrument as valid if two teachers give the same assessment on students. Experimental results show that the same two teachers in assessing students. Thus be valid assessment instrument.